Нефть Южно-Табаганского месторождения - Немировская Г. Б. Галина Борисовна; Сечина Т. В. Тамара Владимировна; Коробочкина В. Г. Вера Геннадьевна; Нурмухамедова В. К. Валентина Константиновна; Нурмухамедов Р. М. Равиль Мамедович (Томск, 1989)
Деп. в ЦНИИТЭНефтехим 04.05.89, № 85-НХ-89.